2003
DOI: 10.1021/nl034054t
|View full text |Cite
|
Sign up to set email alerts
|

Highly Luminescent Water-Soluble CdTe Quantum Dots

Abstract: Colloidal CdTe quantum dots prepared in TOP/DDA (trioctylphosphine/dodecylamine) are transferred into water by the use of amino− ethanethiol•HCl (AET) or mercaptopropionic acid (MPA). This results in an increase in the photoluminescence quantum efficiency and a longer exciton lifetime. For the first time, water-soluble semiconductor nanocrystals presenting simultaneously high band-edge photoluminescence quantum efficiencies (as high as 60% at room temperature), monoexponential exciton decays, and no observable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
369
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 439 publications
(393 citation statements)
references
References 28 publications
(77 reference statements)
23
369
1
Order By: Relevance
“…The higher luminescence efficiency is ascribed to a better surface passivation by the thiol capping molecules. For CdTe QDs with an optimized QE after synthesis in TOP/ DDA, capping exchange with AET has been shown to yield water-soluble QDs with a QE as high as 60% 13 which is in agreement with the presently observed beneficial effect of capping exchange with a variety of thiol molecules.…”
Section: Capping Exchange With Thiols Of Top/dda-cappedsupporting
confidence: 84%
See 2 more Smart Citations
“…The higher luminescence efficiency is ascribed to a better surface passivation by the thiol capping molecules. For CdTe QDs with an optimized QE after synthesis in TOP/ DDA, capping exchange with AET has been shown to yield water-soluble QDs with a QE as high as 60% 13 which is in agreement with the presently observed beneficial effect of capping exchange with a variety of thiol molecules.…”
Section: Capping Exchange With Thiols Of Top/dda-cappedsupporting
confidence: 84%
“…This defect-related emission originates from surface defects since recapping with AET removes this type of emission almost completely. 13 This defect-related emission is also observed in efficient samples since the QDs are not all chemically identical.…”
Section: Capping Exchange With Thiols Of Top/dda-cappedmentioning
confidence: 82%
See 1 more Smart Citation
“…To date, most of the reported X-ray diffraction profiles of CdTe QDs prepared in the water have shown that they have the zinc blende crystal structure [46]. Three strong peaks will generally be observed with 2q values at 23.7 , 39.3 and 46.4 corresponding to the (111), (220), and (311) planes [47]. The peak at 23.7 will generally be more intense than the other two peaks.…”
Section: Preparation Of Cdte Quantum Dots In the Aqueous Phasementioning
confidence: 99%
“…Several surfactants have been used for synthesizing CdTe quantum dots in the aqueous phase, namely, thioglycolic acid (TGA) [48][49][50], mercaptopropionic acid (MPA) [47], mercaptosucinnic acid (MSA) [51][52], glutathione (GSH) [53], and cysteine (Cys) [54]. TGA, MPA, and MSA are short stabilizing agents and they are commonly used to fabricate water-dispersible CdTe QDs in a one-pot synthesis.…”
Section: Preparation Of Cdte Quantum Dots In the Aqueous Phasementioning
confidence: 99%